Synthesis of ZnO Nanocrystals with Hexagonal (Wurtzite) Structure in Water Using Microwave Irradiation (Journal of Sciences, Islamic Republic of Iran)
Nanocrystals of ZnO were prepared by microwave irradiation using Zn (II) acetate and triethanol amin (TEA) as the starting materials and water as solvent. The nanocrystals of ZnO with hexagonal (Wurtzite) structure were characterized by X-ray powder diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), UV-Vis absorption and FTIR Spectroscopy techniques.